In-situ secondary growth of nanocube-based Prussian-blue film as an ultrasensitive biosensor - Liu, Yu; Peng, J.; Jiang, D.; Chu, Z.; Jin, W. (Elsevier Ltd, 2017)
A regular nanostructure has been widely confirmed to result ina marked improvement in material performance in biosensing applications. In the present study, a regular nanostructured Prussian blue (PB) film with two heterogeneous crystal layers was synthesized in-situ using a secondary growth method. A PB seed layer was first controlled to form uniform cube-like crystal nuclei through an ultrasonic reaction with a single reactant. Then, well-defined 100 nm PB nanocubes were further crystallized on this seed layer using a self-assembly approach. In order to accelerate the electron transfer rate during the enzyme reaction for glucose detection, the graphene was used as the main cross-linker to immobilize glucose oxidase on the PB film. The as-prepared biosensor exhibited high electrocatalysis and electron conductivity for the detection of trace glucose with a sensitivity of 141.5 µA mM-1 cm-2, as well as excellent anti-interference ability in the presence of ascorbic acid and uric acid under a low operation potential of -0.05 V.